Vai trò trung gian của hình ảnh nhận thức và sự nhận dạng với điểm đến lên mối quan hệ trách nhiệm xã hội điểm đến và hành vi có trách nhiệm với môi trường của du khách tại Thành phố Đà Nẵng - Nguyễn Thị Kim , Huệ; Nguyễn Thị , Lộc; Nguyễn Thị , Hồng; Đặng Thị Kim , Thoa (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The necessity for sustainable tourism development leads to concern about tourists’ environmentally responsible behaviour (ERB) and destination social responsibility (DSR). This study investigates the impact of DSR perception on tourists’ ERB through cognitive destination image and tourist-destination identification. The research surveyed 393 tourists visiting Da Nang city. The research model is evaluated via analysis structural model SEM. The result indicates that there are direct positive effects of DSR perception on both the cognitive image and tourist-destination identification, while the cognitive image and identification with destination impact ERB of visitors. Mediation test findings demonstrated that the cognitive image and tourist-destination identification mediate the effect of perceived DSR and ERB of tourists.
Keywords: Environmentally responsible behavior; Social responsibility; Identification; Destination image